DEMOKRASI DALAM PEMIKIRAN POLITIK MUHAMMAD NATSIR (1945-1950) - Habibul Wahyudi; Muchid " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Democracy is commonly discussed and often debated. Talk of democracy hasexisted since 2500 years ago in Greece , in the city of Athens . Many countries in theworld with democratic systems , including Indonesia, the largest Muslim country in theworld . This research will raise the idea of democracy offered by a politician andMuslim intellectuals , Muhammad Natsir . Natsir reject the spirit of modern democracybackgrounds Western secular culture . Because Natsir considers it is not in accordancewith the guidance and teachings of Islam . The purpose of this study are : First , analyzeand explain about democracy in the political thought of Muhammad Natsir (1945-1950). Second , the view expressed by Muhammad Natsir on Election (voting ) .The method used in this research is qualitative research analysis model isdescriptive. By collecting and interpreting the data and then analyze and examine itmore clearly as factors related to the phenomenon under investigation, in this caseliterature be related deepen the political thought of Muhammad Natsir on Democracy.Thus, this study also called library research. Based on the findings of this study showthat: First, democracy is an elaboration of the theistic God's sovereignty and thesovereignty of the people. In the opinion of Natsir, Islam is not a full democracyadherents nor theocracy whole, Islam is Islam. And the question of democracy theisticstated by Muhammad Natsir is that the ideas of Islam in the state could accept the rulesof the secular (reason, intuition, experience), then Islam complete with relevation(revelation). Secondly, Based on democratic practices related to the General Electionthen Natsir view of the election should be carried out with a record of consensusagreement must be contained.Keywords : Political Thought , Democracy Theistic , Muhammad Natsir .